2008
DOI: 10.1111/j.1469-7580.2008.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of the mandibular condylar cartilage in human specimens of 10–15 weeks’ gestation

Abstract: This study analyses some morphological and histological aspects that could have a role in the development of the condylar cartilage (CC). The specimens used were serial sections from 49 human fetuses aged 10-15 weeks. In addition, 3D reconstructions of the mandibular ramus and the CC were made from four specimens. During weeks 10-11 of development, the vascular canals (VC) appear in the CC and the intramembranous ossification process begins. At the same time, in the medial region of the CC, chondroclasts appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Mérida‐Velasco et al () reported detailed observations of the early developmental process of VCs. They suggested that the mesenchymal invagination forming VC appears during 10–11 weeks of gestation and that the deepest posterolateral VC was completely surrounded by the hypertrophic chondrocytes at 12–13 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mérida‐Velasco et al () reported detailed observations of the early developmental process of VCs. They suggested that the mesenchymal invagination forming VC appears during 10–11 weeks of gestation and that the deepest posterolateral VC was completely surrounded by the hypertrophic chondrocytes at 12–13 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the mesenchymal invagination forming VC appears during 10–11 weeks of gestation and that the deepest posterolateral VC was completely surrounded by the hypertrophic chondrocytes at 12–13 weeks of gestation. All the VCs that Mérida‐Velasco et al () described contained blood vessels. Thus, the VCs that Mérida‐Velasco et al () described seemed to correspond to the VCs but not to the PVCs in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations